A method for preparing antibacterial viscose fiber

By using polyanionic polymer dispersant with alkaline thickening effect, the gel protective layer is formed, which solves the problem of zinc oxide dissolving in strong alkali and strong acid environments, and improves the zinc oxide retention rate in antibacterial viscose fibers and Antibacterial properties.

CN118932516BActive Publication Date: 2025-02-14POLY PLASTIC MASTERBATCH SUZHOU
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411420314.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-02-14
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

When using the raw liquid mixing method to produce antibacterial viscose fibers, zinc oxide, as an antibacterial agent, is easily dissolved during the strong alkali dissolution and strong acid solidification bath produced by viscose fiber, resulting in zinc ions precipitation and reducing antibacterial properties due to its amphoteric oxide properties. .

Method used

Use polyanionic polymer with alkaline thickening effect as dispersant to mix zinc oxide with it to form an antibacterial slurry, and add viscose spinning raw liquid during spinning to form a gel protective layer to prevent zinc oxide from being Acid-base erosion.

Benefits of technology

The retention rate and antibacterial effect of zinc oxide in fibers is significantly improved, ensuring the stability of antibacterial viscose fibers and excellent antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118932516B_ABST
    Figure CN118932516B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of chemical fibers, and relates to a method for preparing antibacterial viscose fiber. After adding an antibacterial slurry with a pH value less than 7 to a viscose spinning stock solution with a pH value greater than 10, spinning is performed to obtain the antibacterial viscose fiber, wherein the antibacterial slurry contains zinc oxide and a dispersant, and the dispersant is a polyanionic polymer with an alkaline thickening effect. The present invention utilizes the characteristics of low viscosity and easy dispersion of the polyanionic polymer with an alkaline thickening effect at low pH to prepare the antibacterial slurry with zinc oxide; during the spinning process, the polyanionic polymer with an alkaline thickening effect rapidly thickens under the strong alkali action of the viscose spinning stock solution, forming a gel protective layer, which effectively isolates the acid-base environment from erosion of zinc oxide, avoids the dissolution of zinc oxide and the precipitation of zinc ions, and significantly improves the retention rate of zinc oxide in the fiber and the antibacterial effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical fibers and relates to a method for preparing antibacterial viscose fibers. Background Art

[0002] As a chemical fiber with a long history and wide application, viscose fiber occupies an important position in many fields such as textile, medical treatment, and hygiene due to its unique physical and chemical properties. However, with the improvement of people's health awareness and the increase of environmental protection needs, the shortcomings of traditional viscose fiber in antibacterial performance have gradually emerged, making it difficult to meet the market demand for high-performance antibacterial fibers.

[0003] Currently, the development of antibacterial viscose fiber has become one of the hot topics in industry research. By introducing antibacterial agents into viscose fibers, its antibacterial properties can be effectively improved, thereby inhibiting bacterial growth, preventing odor, and improving product hygiene standards and user experience.

[0004] There are two main methods for producing antibacterial viscose fibers. One is to use the post-finishing method, that is, to apply antibacterial agents to the finished viscose fibers to give them antibacterial functions. The other is to blend the antibacterial agents with the viscose fibers and produce antibacterial viscose fibers through wet spinning. This method is called the stock solution mixing method.

[0005] With the development of technology, the stock solution mixing method has great development prospects due to its simplicity. For example, patent CN115613359B discloses an antibacterial protein modified viscose fiber and its manufacturing process. The patent mixes carboxymethyl cellulose, chitosan and collagen, adds ethanol-diluted isocyanate crosslinking agent and silicone surfactant to make a solution, grafts the viscose fiber, washes and dries it, and obtains antibacterial viscose fiber; for another example, patent application CN110284209A discloses a temperature-controlled, antibacterial and other multifunctional viscose fiber, its preparation method and fabric. The patent firstly mixes phase change capsule emulsion and graphene dispersion. The spinning solution is mixed with the viscose spinning stock solution to obtain a spinning solution, and then the spinning solution enters a coagulation bath through a spinneret to precipitate primary fibers, which are then stretched and wound to obtain antibacterial viscose fibers. For example, patent application CN109112656A discloses a method for preparing a high-binding antibacterial viscose fiber material, which first places deionized water, polyvinyl alcohol, zinc sulfate, and aluminum sulfate in a beaker, stirs and mixes them, and then ultrasonicates them, and then adds ammonia water for aging and other treatments to obtain a powder, and then makes a gel solution with deionized water, acetic acid solution, etc., and spins it with the viscose spinning solution to prepare antibacterial viscose fibers.

[0006] Although the stock solution mixing method has attracted much attention due to its simplicity, it still faces some technical challenges in practical application, especially when using certain specific antimicrobial agents such as zinc oxide.

[0007] Zinc oxide, as an inorganic antimicrobial agent, has been widely studied for its good antimicrobial properties. However, when using the stock solution mixing method to produce antimicrobial viscose fiber, if zinc oxide is used as an antimicrobial agent, due to its amphoteric oxide characteristics, zinc oxide will quickly dissolve into zinc ions during the strong alkaline dissolution and strong acid coagulation bath processes of viscose fiber production, causing the zinc ions to be extracted during the spinning process, thereby reducing the zinc content in the final product and insufficient antimicrobial performance. At present, general inorganic oxide surface treatment methods, such as the sol-gel method, produce a layer of other oxides on the surface of the inorganic oxide. This method itself uses controlled precipitation under pH. The viscose fiber production process has both a strong alkaline dissolution process and a strong acid precipitation process. The encapsulated oxide is difficult to stabilize under strong acid and alkali, resulting in re-decomposition and failure.

[0008] Therefore, it is necessary to develop a method that can effectively protect zinc oxide from acid and alkali erosion and dissolution during the dope mixing spinning process. Summary of the invention

[0009] The purpose of the present invention is to solve the problems existing in the prior art and provide a method for preparing antibacterial viscose fiber.

[0010] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0011] A method for preparing antibacterial viscose fiber comprises the following steps: adding an antibacterial slurry with a pH value less than 7 to a viscose spinning stock solution with a pH value greater than 10, and spinning the solution to obtain the antibacterial viscose fiber, wherein the antibacterial slurry contains zinc oxide and a dispersant, and the dispersant is a polyanionic polymer with an alkaline thickening effect.

[0012] As the preferred technical solution:

[0013] In the method for preparing the antibacterial viscose fiber as described above, the zinc oxide is one or more of active zinc oxide, direct zinc oxide and indirect zinc oxide.

[0014] In the method for preparing the antibacterial viscose fiber as described above, the dispersant is one or more of polyacrylic acid, polymethacrylic acid and polyanionic cellulose.

[0015] The method for preparing an antibacterial viscose fiber as described above, in terms of weight percentage, the components and contents in the antibacterial slurry are: 10-20 parts of zinc oxide, 20-35 parts of dispersant, 0.5-1 part of defoaming agent, 0.5-1 part of acidic pH regulator (adding acidic pH regulator can improve the fluidity of antibacterial slurry), and 40-60 parts of deionized water.

[0016] In the method for preparing the antibacterial viscose fiber as described above, the defoaming agent is one or more of polysiloxane, polyether siloxane copolymer and polyacrylate.

[0017] As described above, a method for preparing an antibacterial viscose fiber, the preparation process of the antibacterial slurry is: after pre-dispersing the components except zinc oxide, zinc oxide is added thereto for dispersion, and then added to a sand mill for grinding to reduce the average particle size of zinc oxide to less than 1 μm, thereby obtaining the antibacterial slurry, wherein the temperature of the whole process is controlled at 20-60°C, pre-dispersion refers to stirring at a speed of 500-1000rpm for 20-30min, dispersion refers to stirring at a speed of 1000-1500rpm for 30-60min, and grinding refers to grinding at a speed of 1000-2000rpm in a sand mill containing 0.4-0.6mm zirconium beads for 1-5h.

[0018] In the preparation method of the antibacterial viscose fiber as described above, the addition amount of zinc oxide is 2-5wt% of the solid content of the viscose fiber, the retention rate of zinc oxide in the antibacterial viscose fiber (the retention rate of zinc oxide in the antibacterial viscose fiber = the actual content of zinc oxide in the antibacterial viscose fiber / theoretical content of zinc oxide in the antibacterial viscose fiber × 100%, the actual content of zinc oxide in the antibacterial viscose fiber is measured by ICP-OES (inductively coupled plasma emission spectrometer)) is ≥50%, and the antibacterial rate of the antibacterial viscose fiber against Escherichia coli, Staphylococcus aureus, and Candida albicans (detected by the national standard GB / T 20944.3-2008 oscillation method) is ≥70%, and the antibacterial property of the antibacterial viscose fiber is excellent.

[0019] Principle of the invention:

[0020] like Figure 1 As shown, the polyanionic polymer with alkaline thickening effect selected in the present invention has a multi-carboxyl property and exhibits a low viscosity under low pH conditions (pH less than 7), which enables it to effectively disperse zinc oxide particles to form a uniform antibacterial slurry. When the antibacterial slurry is added to a viscose spinning stock solution with a pH value greater than 10, the polyanionic polymer with alkaline thickening effect rapidly thickens under the action of a strong base. This thickening effect forms a dense gel protective layer on the surface of the zinc oxide particles. The gel layer not only effectively isolates the direct erosion of zinc oxide by the acid-base environment, but also fixes part of the zinc ions generated by the strong alkali dissolution through cross-linking, thereby reducing the precipitation of zinc ions.

[0021] The presence of the gel protective layer significantly improves the retention rate of zinc oxide in the fiber because H + It is difficult to penetrate the gel layer to contact the zinc oxide in the core layer. At the same time, according to Fick's second diffusion law, H + and OH -The diffusion flux is hindered by the gel layer and cannot reach the surface of zinc oxide quickly, thereby further inhibiting the erosion of zinc oxide by acids and alkalis. This protection mechanism ensures the stability of zinc oxide during the spinning process, thereby improving the antibacterial effect and service life of the antibacterial viscose fiber.

[0022] Beneficial effects:

[0023] (1) The present invention utilizes the low viscosity and easy dispersion of polyanionic polymers with alkaline thickening effect at low pH to prepare zinc oxide into an antibacterial slurry; during the spinning process, the polyanionic polymers with alkaline thickening effect rapidly thicken under the action of the strong alkali in the viscose spinning solution to form a gel protective layer, which effectively isolates the corrosion of zinc oxide by the acid-base environment, avoids the dissolution of zinc oxide and the precipitation of zinc ions, and significantly improves the retention rate of zinc oxide in the fiber and the antibacterial effect.

[0024] (2) The antibacterial viscose fiber prepared by the present invention has excellent antibacterial properties and stability, and can be widely used in textile, medical, health and other fields, and has broad market prospects and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the process of a polyanionic polymer with alkaline thickening effect dispersing zinc oxide at low pH and forming a gel protective layer on the surface of zinc oxide in a strong alkaline environment;

[0026] Figure 2 This is a physical picture of the antibacterial slurry of Example 1 of the present invention;

[0027] Figure 3 This is a physical picture of the antibacterial slurry of Example 1 of the present invention under strong alkaline conditions (adjusted to 11 by adding a 5wt% sodium hydroxide aqueous solution);

[0028] Figure 4 The viscosity curve of the antibacterial slurry of Example 1 of the present invention under acidic conditions (adjusted to 6 by adding a 5 wt % hydrochloric acid aqueous solution);

[0029] Figure 5 This is a viscosity curve of the antibacterial slurry of Example 1 of the present invention under strong alkaline conditions (adjusted to 11 by adding 5 wt % sodium hydroxide aqueous solution). DETAILED DESCRIPTION

[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0031] Example 1

[0032] A method for preparing antibacterial viscose fiber, the specific steps are as follows:

[0033] (1) Preparation of raw materials;

[0034] Dispersant: polyacrylic acid, manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., product number: S51652;

[0035] Defoaming agent: polysiloxane, manufactured by BYK Chemical Company, model BYKA530;

[0036] Acidic pH regulator: hydrochloric acid aqueous solution, concentration 5wt%;

[0037] Deionized water;

[0038] Zinc oxide: activated zinc oxide, manufactured by Jinxin Chemical Co., Ltd.

[0039] Viscose spinning solution: pH value is 11;

[0040] (2) preparing antibacterial slurry;

[0041] At 25°C, a dispersant, a defoamer, an acidic pH regulator, and deionized water were stirred at 1000 rpm for 60 minutes, zinc oxide was added thereto, stirred at 2000 rpm for 90 minutes, and then ground at 2500 rpm for 2 hours in a sand mill containing 0.4-0.6 mm zirconium beads to reduce the average particle size of zinc oxide to 0.55 μm, thereby obtaining an antibacterial slurry with a pH value of 6.5;

[0042] Antibacterial slurry Figure 2 As shown; the viscosity curve of the antibacterial slurry under acidic conditions is as follows Figure 4 As shown; the actual antibacterial slurry under strong alkaline conditions is as follows Figure 3 The viscosity curve is shown as Figure 5 As shown; by weight, the content of each component in the antibacterial slurry is: 20 parts of dispersant, 0.5 parts of defoamer, 0.5 parts of acidic pH regulator, 40 parts of deionized water, and 20 parts of zinc oxide;

[0043] (3) Preparation of antibacterial viscose fiber;

[0044] After adding the antibacterial slurry into the viscose spinning stock solution, spinning is carried out to obtain the antibacterial viscose fiber; wherein the added amount of zinc oxide is 2wt% of the solid content of the viscose fiber.

[0045] The retention rate of zinc oxide in the final antibacterial viscose fiber is 80%; the antibacterial rate of the antibacterial viscose fiber against Escherichia coli is 95%, the antibacterial rate against Staphylococcus aureus is 95%, and the antibacterial rate against Candida albicans is 90%.

[0046] Comparative Example 1

[0047] A method for preparing viscose fiber is basically the same as Example 1, except that the dispersant is replaced by styrene maleic anhydride polyether modified polymer dispersant BYK-190 (manufacturer: BYK Chemical Company); the average particle size of zinc oxide after grinding in step (2) is reduced to 0.22 μm, and the pH value of the obtained antibacterial slurry is 6.4.

[0048] The retention rate of zinc oxide in the final viscose fiber is 30%; the antibacterial rate of viscose fiber against Escherichia coli is 50%, the antibacterial rate against Staphylococcus aureus is 62%, and the antibacterial rate against Candida albicans is 60%.

[0049] Comparative Example 2

[0050] A method for preparing viscose fiber is basically the same as that in Example 1, except that the dispersant is replaced by a sodium polyacrylate dispersant HPD 196 (manufacturer: BASF Corporation); the average particle size of zinc oxide after grinding in step (2) is reduced to 0.24 μm, and the pH value of the obtained antibacterial slurry is 6.3.

[0051] The retention rate of zinc oxide in the final viscose fiber is 45%; the antibacterial rate of viscose fiber against Escherichia coli is 68%, the antibacterial rate against Staphylococcus aureus is 60%, and the antibacterial rate against Candida albicans is 60%.

[0052] Compared with Example 1, Comparative Example 1 and Comparative Example 2, the retention rate of zinc oxide in the finally obtained viscose fiber is significantly reduced, and the antibacterial effect of the viscose fiber is significantly deteriorated. This is because the commercial dispersant used in Comparative Example 1 and Comparative Example 2 cannot effectively disperse the zinc oxide particles under low pH conditions, and it is difficult to form a uniform and stable antibacterial slurry. It cannot quickly thicken under the action of a strong alkali to form a dense gel protective layer. Without the isolation effect of the gel protective layer, the acid-base environment can directly corrode the zinc oxide, resulting in a large amount of zinc ions precipitating, which significantly reduces the retention rate of zinc oxide in the finally obtained viscose fiber; at the same time, due to the reduction of zinc ions, the antibacterial effect of the viscose fiber is also significantly deteriorated, and the bacterial growth cannot be effectively inhibited, and the antibacterial rate of Escherichia coli, Staphylococcus aureus and Candida albicans is significantly reduced.

[0053] Example 2

[0054] A method for preparing antibacterial viscose fiber, the specific steps are as follows:

[0055] (1) Preparation of raw materials;

[0056] Dispersant: polymethacrylic acid, manufactured by Adamas, product number 101681CC;

[0057] Defoaming agent: polyether siloxane, manufacturer: Evonik Tego Chemical Co., Ltd., model: Tego-825;

[0058] Acidic pH regulator: sulfuric acid aqueous solution, concentration 5wt%;

[0059] Deionized water;

[0060] Zinc oxide: indirect zinc oxide, the manufacturer is Jinxin Chemical Co., Ltd.;

[0061] Viscose spinning solution: pH value is 13;

[0062] (2) preparing antibacterial slurry;

[0063] At 20°C, a dispersant, a defoamer, an acidic pH regulator, and deionized water were stirred at 1000 rpm for 60 minutes, zinc oxide was added thereto, stirred at 2000 rpm for 60 minutes, and then ground at 2500 rpm for 2 hours in a sand mill containing 0.4-0.6 mm zirconium beads to reduce the average particle size of zinc oxide to 0.7 μm, thereby obtaining an antibacterial slurry with a pH value of 6.7;

[0064] The contents of the components in the antibacterial slurry are as follows by weight: 35 parts of dispersant, 0.5 parts of defoamer, 0.5 parts of acidic pH regulator, 40 parts of deionized water, and 20 parts of zinc oxide;

[0065] (3) Preparation of antibacterial viscose fiber;

[0066] After adding the antibacterial slurry into the viscose spinning stock solution, spinning is carried out to obtain the antibacterial viscose fiber; wherein the added amount of zinc oxide is 2wt% of the solid content of the viscose fiber.

[0067] The retention rate of zinc oxide in the final antibacterial viscose fiber is 75%; the antibacterial rate of the antibacterial viscose fiber against Escherichia coli is 78%, the antibacterial rate against Staphylococcus aureus is 85%, and the antibacterial rate against Candida albicans is 80%.

[0068] Example 3

[0069] A method for preparing antibacterial viscose fiber, the specific steps are as follows:

[0070] (1) Preparation of raw materials;

[0071] Dispersant: polyacrylic acid, manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., product number: S51652;

[0072] Defoaming agent: polysiloxane, manufactured by BYK Chemical Company, model BYKA530;

[0073] Acidic pH regulator: hydrochloric acid aqueous solution, concentration 5wt%;

[0074] Deionized water;

[0075] Zinc oxide: activated zinc oxide, manufactured by Jinxin Chemical Co., Ltd.

[0076] Viscose spinning solution: pH value is 11;

[0077] (2) preparing antibacterial slurry;

[0078] At 25°C, a dispersant, a defoamer, an acidic pH regulator, and deionized water were stirred at 900 rpm for 90 minutes, zinc oxide was added thereto, stirred at 1000 rpm for 90 minutes, and then ground at 2000 rpm for 1 hour in a sand mill containing 0.4-0.6 mm zirconium beads to reduce the average particle size of zinc oxide to 0.4 μm, thereby obtaining an antibacterial slurry with a pH value of 6.5;

[0079] The contents of the components in the antibacterial slurry are as follows by weight: 20 parts of dispersant, 1 part of defoamer, 1 part of acidic pH regulator, 50 parts of deionized water, and 20 parts of zinc oxide;

[0080] (3) Preparation of antibacterial viscose fiber;

[0081] After adding the antibacterial slurry into the viscose spinning stock solution, spinning is carried out to obtain the antibacterial viscose fiber; wherein the added amount of zinc oxide is 2wt% of the solid content of the viscose fiber.

[0082] The retention rate of zinc oxide in the final antibacterial viscose fiber is 70%; the antibacterial rate of the antibacterial viscose fiber against Escherichia coli is 75%, the antibacterial rate against Staphylococcus aureus is 90%, and the antibacterial rate against Candida albicans is 88%.

[0083] Example 4

[0084] A method for preparing antibacterial viscose fiber, the specific steps are as follows:

[0085] (1) Preparation of raw materials;

[0086] Dispersant: polyanionic cellulose, manufacturer: Shanghai MacLean Biochemical Technology Co., Ltd., product number: P875779;

[0087] Defoaming agent: polyacrylate, manufactured by BASF, model EFKA FL 3772;

[0088] Acidic pH regulator: citric acid aqueous solution, concentration 5wt%;

[0089] Deionized water;

[0090] Zinc oxide: direct zinc oxide, the manufacturer is Jinxin Chemical Co., Ltd.;

[0091] Viscose spinning solution: pH value is 13;

[0092] (2) preparing antibacterial slurry;

[0093] At 20°C, a dispersant, a defoamer, an acidic pH regulator, and deionized water were stirred at 800 rpm for 90 minutes, zinc oxide was added thereto, stirred at 3000 rpm for 90 minutes, and then ground at 2000 rpm for 3 hours in a sand mill containing 0.4-0.6 mm zirconium beads to reduce the average particle size of zinc oxide to 0.62 μm, thereby obtaining an antibacterial slurry with a pH value of 6.8;

[0094] The contents of the components in the antibacterial slurry are as follows by weight: 20 parts of dispersant, 1 part of defoamer, 1 part of acidic pH regulator, 40 parts of deionized water, and 10 parts of zinc oxide;

[0095] (3) Preparation of antibacterial viscose fiber;

[0096] After adding the antibacterial slurry into the viscose spinning stock solution, spinning is carried out to obtain the antibacterial viscose fiber; wherein the added amount of zinc oxide is 3wt% of the solid content of the viscose fiber.

[0097] The retention rate of zinc oxide in the final antibacterial viscose fiber is 70%; the antibacterial rate of the antibacterial viscose fiber against Escherichia coli is 75%, the antibacterial rate against Staphylococcus aureus is 75%, and the antibacterial rate against Candida albicans is 80%.

[0098] Example 5

[0099] A method for preparing antibacterial viscose fiber, the specific steps are as follows:

[0100] (1) Preparation of raw materials;

[0101] Dispersant: a mixture of polyacrylic acid (manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., catalog number: S51652) and polymethacrylic acid (manufacturer: Adamas, catalog number: 101681CC) in a mass ratio of 1:1;

[0102] Defoaming agent: polysiloxane, manufactured by BYK Chemical Company, model BYKA530;

[0103] Acidic pH regulator: hydrochloric acid aqueous solution, concentration 5wt%;

[0104] Deionized water;

[0105] Zinc oxide: activated zinc oxide, manufactured by Jinxin Chemical Co., Ltd.

[0106] Viscose spinning solution: pH value is 11;

[0107] (2) preparing antibacterial slurry;

[0108] At 30°C, a dispersant, a defoamer, an acidic pH regulator, and deionized water were stirred at 500 rpm for 70 minutes, zinc oxide was added thereto, stirred at 2000 rpm for 120 minutes, and then ground at 3000 rpm for 1 hour in a sand mill containing 0.4-0.6 mm zirconium beads to reduce the average particle size of zinc oxide to 0.65 μm, thereby obtaining an antibacterial slurry with a pH value of 6.7;

[0109] The contents of the components in the antibacterial slurry are as follows by weight: 20 parts of dispersant, 1 part of defoamer, 0.5 parts of acidic pH regulator, 45 parts of deionized water, and 20 parts of zinc oxide;

[0110] (3) Preparation of antibacterial viscose fiber;

[0111] After adding the antibacterial slurry into the viscose spinning stock solution, spinning is carried out to obtain the antibacterial viscose fiber; wherein the added amount of zinc oxide is 5wt% of the solid content of the viscose fiber.

[0112] The retention rate of zinc oxide in the final antibacterial viscose fiber is 67%; the antibacterial rate of the antibacterial viscose fiber against Escherichia coli is 75%, the antibacterial rate against Staphylococcus aureus is 85%, and the antibacterial rate against Candida albicans is 85%.

[0113] Example 6

[0114] A method for preparing antibacterial viscose fiber, the specific steps are as follows:

[0115] (1) Preparation of raw materials;

[0116] Dispersant: polyacrylic acid, manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., product number: S51652;

[0117] Defoaming agent: a mixture of polysiloxane (polysiloxane, manufactured by BYK Chemical Company, model number BYKA530) and polyacrylate (manufactured by BASF, model number EFKA FL 3772) in a mass ratio of 1:1;

[0118] Acidic pH regulator: hydrochloric acid aqueous solution, concentration 5wt%;

[0119] Deionized water;

[0120] Zinc oxide: activated zinc oxide, manufactured by Jinxin Chemical Co., Ltd.

[0121] Viscose spinning solution: pH value is 11;

[0122] (2) preparing antibacterial slurry;

[0123] At 30°C, a dispersant, a defoamer, an acidic pH regulator, and deionized water were stirred at 500 rpm for 60 minutes, zinc oxide was added thereto, stirred at 2000 rpm for 90 minutes, and then ground at 2500 rpm for 2 hours in a sand mill containing 0.4-0.6 mm zirconium beads to reduce the average particle size of zinc oxide to 0.55 μm, thereby obtaining an antibacterial slurry with a pH value of 6.5;

[0124] The contents of the components in the antibacterial slurry are as follows by weight: 25 parts of dispersant, 0.5 parts of defoamer, 1 part of acidic pH regulator, 50 parts of deionized water, and 20 parts of zinc oxide;

[0125] (3) Preparation of antibacterial viscose fiber;

[0126] After adding the antibacterial slurry into the viscose spinning stock solution, spinning is carried out to obtain the antibacterial viscose fiber; wherein the added amount of zinc oxide is 5wt% of the solid content of the viscose fiber.

[0127] The retention rate of zinc oxide in the final antibacterial viscose fiber is 65%; the antibacterial rate of the antibacterial viscose fiber against Escherichia coli is 70%, the antibacterial rate against Staphylococcus aureus is 75%, and the antibacterial rate against Candida albicans is 72%.

[0128] Example 7

[0129] A method for preparing antibacterial viscose fiber, the specific steps are as follows:

[0130] (1) Preparation of raw materials;

[0131] Dispersant: polyacrylic acid, manufacturer: Shanghai Yuanye Biotechnology Co., Ltd., product number: S51652;

[0132] Defoaming agent: polysiloxane, manufactured by BYK Chemical Company, model BYKA530;

[0133] Acidic pH regulator: hydrochloric acid aqueous solution, concentration 5wt%;

[0134] Deionized water;

[0135] Zinc oxide: a mixture of active zinc oxide and direct zinc oxide in a mass ratio of 2:1. The manufacturers of active zinc oxide and direct zinc oxide are both Jinxin Chemical Co., Ltd.

[0136] Viscose spinning solution: pH value is 11;

[0137] (2) preparing antibacterial slurry;

[0138] At 30°C, a dispersant, a defoamer, an acidic pH regulator, and deionized water were stirred at 700 rpm for 60 minutes, zinc oxide was added thereto, stirred at 2000 rpm for 90 minutes, and then ground at 2500 rpm for 3 hours in a sand mill containing 0.4-0.6 mm zirconium beads to reduce the average particle size of zinc oxide to 0.6 μm, thereby obtaining an antibacterial slurry with a pH value of 6.4;

[0139] The contents of the components in the antibacterial slurry are as follows by weight: 30 parts of dispersant, 0.5 parts of defoamer, 0.5 parts of acidic pH regulator, 60 parts of deionized water, and 20 parts of zinc oxide;

[0140] (3) Preparation of antibacterial viscose fiber;

[0141] After adding the antibacterial slurry into the viscose spinning stock solution, spinning is carried out to obtain the antibacterial viscose fiber; wherein the added amount of zinc oxide is 5wt% of the solid content of the viscose fiber.

[0142] The retention rate of zinc oxide in the final antibacterial viscose fiber is 75%; the antibacterial rate of the antibacterial viscose fiber against Escherichia coli is 90%, the antibacterial rate against Staphylococcus aureus is 90%, and the antibacterial rate against Candida albicans is 85%.

[0143] Comparative Example 3

[0144] A method for preparing viscose fiber is basically the same as Example 7, except that the dispersant is replaced by styrene maleic anhydride polyether modified polymer dispersant BYK-190 (manufacturer: BYK Chemical Company); the average particle size of zinc oxide after grinding in step (2) is reduced to 0.43 μm, and the pH value of the obtained antibacterial slurry is 6.4.

[0145] The retention rate of zinc oxide in the final viscose fiber is 40%; the antibacterial rate of viscose fiber to Escherichia coli is 55%, the antibacterial rate to Staphylococcus aureus is 40%, and the antibacterial rate to Candida albicans is 55%.

[0146] Compared with Example 7, the retention rate of zinc oxide in the final viscose fiber obtained in Comparative Example 3 is significantly reduced, and the antibacterial effect of the viscose fiber is significantly deteriorated. This is because the commercial dispersant used in Comparative Example 3 cannot effectively disperse the zinc oxide particles under low pH conditions, and it is difficult to form a uniform and stable antibacterial slurry. It cannot quickly thicken under the action of a strong alkali to form a dense gel protective layer. Without the isolation effect of the gel protective layer, the acid-base environment can directly corrode the zinc oxide, resulting in a large amount of zinc ions precipitated, which significantly reduces the retention rate of zinc oxide in the final viscose fiber. At the same time, due to the reduction of zinc ions, the antibacterial effect of the viscose fiber is also significantly deteriorated, and it cannot effectively inhibit bacterial growth. The antibacterial rate of Escherichia coli, Staphylococcus aureus and Candida albicans is significantly reduced.

Claims

1. A method for preparing antibacterial viscose fiber, characterized in that: The antibacterial slurry with a pH value of less than 7 is added to a viscose spinning stock solution with a pH value of greater than 10, and then spinning is performed to obtain antibacterial viscose fiber, wherein the antibacterial slurry contains zinc oxide and a dispersant, and the dispersant is a polyanionic polymer with an alkaline thickening effect; The components and contents of the antibacterial slurry are as follows by weight: 10-20 parts of zinc oxide, 20-35 parts of dispersant, 0.5-1 parts of defoamer, 0.5-1 parts of acidic pH regulator, and 40-60 parts of deionized water; The preparation process of the antibacterial slurry is as follows: after pre-dispersing the components except zinc oxide, zinc oxide is added thereto for dispersion, and then added to a sand mill for grinding to reduce the average particle size of zinc oxide to less than 1 μm, thereby obtaining the antibacterial slurry, wherein the temperature of the entire process is controlled at 20-60°C, pre-dispersion refers to stirring at a speed of 500-1000rpm for 20-30min, dispersion refers to stirring at a speed of 1000-1500rpm for 30-60min, and grinding refers to grinding at a speed of 1000-2000rpm in a sand mill containing 0.4-0.6mm zirconium beads for 1-5h.

2. The method for preparing an antibacterial viscose fiber according to claim 1, characterized in that: The zinc oxide is one or more of active zinc oxide, direct zinc oxide and indirect zinc oxide.

3. The method for preparing an antibacterial viscose fiber according to claim 1, characterized in that: The dispersant is one or more of polyacrylic acid, polymethacrylic acid and polyanionic cellulose.

4. The method for preparing an antibacterial viscose fiber according to claim 1, characterized in that: The defoaming agent is one or more of polysiloxane, polyether siloxane copolymer and polyacrylate.

5. The method for preparing antibacterial viscose fiber according to claim 1, characterized in that: The added amount of zinc oxide is 2-5wt% of the solid content of the viscose fiber, the retention rate of zinc oxide in the antibacterial viscose fiber is ≥50%, and the antibacterial rates of the antibacterial viscose fiber to Escherichia coli, Staphylococcus aureus and Candida albicans are all ≥70%.

Citation Information

Patent Citations

  • Preparation method of high combination type antibacterial viscose fiber material

    CN109112656A

  • Multifunctional viscose with functions such as temperature regulation and bacterium resistance, preparation method of viscose and fabric

    CN110284209A

  • Antibacterialtextile material and a preparation method thereof

    CN106893282A

  • Hydrophobic nano zinc oxide powder as well as preparation method and application thereof

    CN110684378A